Analysis of MicroRNA Profile Alterations in Extracellular Vesicles From Mesenchymal Stromal Cells Overexpressing Stem Cell Factor - Zubkova, Ekaterina; Evtushenko, Evgeniy; Beloglazova, Irina; Osmak, German; Koshkin, Phillip; Moschenko, Alexander; Menshikov, Mikhail; Parfyonova, Yelena (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stem/stromal cells (MSCs) represent a promising tool to treat cardiovascular diseases. One mode of action through which MSCs exert their protective effects is secretion of extracellular vesicles (EVs). Recently we demonstrated that rat adipose-derived MSC overexpressing stem cell factor (SCF) can induce endogenous regenerative processes and improve cardiac function. In present work we isolated EVs from intact or SCF-overexpressing rat MSC and analyzed microarray datasets of their miRNA cargo. We uncovered a total of 95 differentially expressed miRNAs and identified 2 miRNAs significantly up-regulated in SCF-MSCs. One of them - rno-miR-344a-2, associated with aging and regulation of a-SMA was also increased in EVs from GFP-MSC that may indicate intrinsic changes in MSC after viral transduction. About 80 miRNA were downregulated in EVs from SCF- or GFP-MSC. We assembled the miRNA-based network and found several nodes of target genes among which Vim Sept3 and Vsnl1 are involved in regulation of cellular migration that consistent with our previous EVs data. Topological analyses of network also revealed among downregulated miRNAs- rno-miRNA-128-3p that regulates plenty of targets presumably associated with chemokine signaling pathways. Overall, our data suggest that genetic modification of MSC have a great impact on their miRNA composition and provide novel insights into the regulatory networks underlying EVs effects.